'Face time' for the first time: Video communication between relatives and junior doctors in the COVID-19 pandemic. Issue 3 (2021) - White, Harriet L; Tuck, Alexander A; Pyrke, Benjamin C; Murphy, Emily; Figg, Katherine; Cartwright, Gwendolen J
No abstract available